Modeling electromagnetic systems - Аikeeva, А.А.; Zhautikov, B.А.; Aydarkhanov, А.М.; Zhanasbayeva, А.S.; Zhautikov, F.B.; Belgibayev, А.S. (Publishing House of the KarSU named after E.A.Buketov, 2014)
The article is devoted to modeling electromagnetic systems which was carried out in a package of the applied ANSYS programs. ANSYS is universal program system of finite element analysis. Modeling and analysis in some areas of the industry allows to avoid expensive and long-lived cycles of development like "projection — manufacture — tests". The system works on the basis of geometric element. Each type of elements uses values of material properties.
Keywords: electromagnet; constant magnet; simulation modeling; Lorentz force; magnetic induction; magnetic intensity